2014
DOI: 10.1161/circulationaha.113.003645
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Endothelial Activation Detected by Molecular Imaging in Obese Nonhuman Primates Coincides With Onset of Insulin Resistance and Progressively Increases With Duration of Insulin Resistance

Abstract: Background Inflammation and insulin resistance (IR) are associated processes that potentiate risk for cardiovascular disease in obesity. The temporal relation between IR and inflammation is not completely characterized. We hypothesized that endothelial cell adhesion molecule (ECAM) expression in large arteries is an early event that coincides with diet-induced obesity and IR in primates. Methods and Results Ten adult male rhesus macaques were studied at baseline and every 4-6 months on high-fat diet (HFD) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 37 publications
5
54
0
Order By: Relevance
“…Next to pigs, the expression of P-selectin and VCAM-1 expression in the carotid of non-human primates has also been recently assessed with UMI. This study shows that endothelial cell adhesion molecule expression in large arteries could be an early event that coincides with diet-induced obesity and insulin resistance in non-human primates [174]. In another recent study on non-human primates with myocardial ischaemia, UMI was shown to be both safe and effective for imaging recent myocardial ischaemia.…”
Section: In Vivo Molecular Imagingmentioning
confidence: 60%
“…Next to pigs, the expression of P-selectin and VCAM-1 expression in the carotid of non-human primates has also been recently assessed with UMI. This study shows that endothelial cell adhesion molecule expression in large arteries could be an early event that coincides with diet-induced obesity and insulin resistance in non-human primates [174]. In another recent study on non-human primates with myocardial ischaemia, UMI was shown to be both safe and effective for imaging recent myocardial ischaemia.…”
Section: In Vivo Molecular Imagingmentioning
confidence: 60%
“…A low level of non-targeted lipid MB signal due to complement-mediated interactions with leukocytes or endothelial cells has been detected in many previous CEU molecular imaging studies of atherosclerosis in murine models but not in our recent studies performed in a non-human primate model. 9,13,38 As mentioned previously, the issue of control MB signal confounded interpretation of the temporal increase in platelet signal since age-dependent increase in MB-A1 was highly significant when expressed as a difference between control MB but not when expressed as a ratio.…”
Section: Discussionmentioning
confidence: 96%
“…Vascular endothelial cells are involved in inflammation and immune response by secreting a series of bioactive substances, such as prostacyclin, NO, endothelin and von Willebrand factor [22]. In addition to the formation of NO which promotes vasodilation, endothelial cells also modulate the migration of leukocytes through releasing inflammatory chemokines, cytokines, and cell surface adhesion molecules [23]. Inflammation, trauma and other stress injuries stimulate endothelial cells to increase vascular permeability and adhesion molecule expression, leading to edema, adhesion of leukocytes, and a subsequent inflammatory cascade reaction [24].…”
Section: Discussionmentioning
confidence: 99%